The Science Teachers’ Communication Behavior in Relation to Students’ Attitude and Performance - Sierto, Maricel E. (Future Science / FSH-PH Publications, 2023)
The purpose of this study was to find out the relationship between the communicative behavior of teachers and the attitudes and performance of students in Science in Sta. Peregrina High School in Balatong B, Pulilan, Bulacan. In particular, the aim of this study was to find answers to the following questions: (1) What is the level Science teachers show in challenging, encouraging and praise, non-verbal support, understanding, and controlling behavior? (2) At what level is the attitude of the students towards science? (3) What is the performance level of students in science subject? (4) Are teachers’ communication and students’ attitudes toward science related to each other? and (5) Are teachers’ communication and students’ performance toward science related to each other? Descriptive quantifiable method of research was utilized in this study. The following conclusions were drawn: (1) Science teachers received very acceptable ratings for challenging, encouraging and praise, non-verbal support, understanding, and controlling behaviour as observed by their students. (2) Students have very acceptable attitudes to Science. (3) Students acquired an acceptable assessment in their Science grade. (4) There was no substantial relationship between challenging, encouraging and praise, controlling behaviour of teachers and the attitude of the students; challenging, encouraging and praise, understanding, and controlling behaviour of teachers and the students’ academic performance. Yet, there was substantial relationship in non-verbal support and understanding behaviour of teachers and attitudes of students.